HIDUP DALAM KOMUNITAS VIRTUAL: STUDI ETNOGRAFI PEREMPUAN BERTATO DI RUANG SIBER - Andreas, Rino; Akhyat Sulkhan, Khumaid; Rizki Rosidah, Dede; Yaqi, Yu (JURNAL ILMU BUDAYA, 2023)
This study aims to look at the construction of tattooed bodies in cyberspace and explain gender relations in the Indonesian Tattoo Women's (PTI) virtual community. This qualitative research uses a virtual ethnographic method that involves the participation of researchers in a community. As a result, the PTI community has a style of interaction that shapes culture in cyberspace. PTI is a place for tattoo lovers, both "women" and "men, to express themselves by uploading photos of tattoos on their body parts. The embodied body, which was originally considered something permanent and natural, has turned into a hybrid body, becoming a cyberbody. Thus, the tattoo phenomenon in cyberspace goes beyond the rigid construction of male/female or feminine/masculine identity issues in real space. Because body identity in the context of cyberspace is fluid, it can be changed, shaped, and even duplicated.